High-Throughput Illumina MiSeq Amplicon Sequencing of Yeast Communities Associated With Indigenous Dairy Products From Republics of Benin and Niger - SESSOU, PHILIPPE; Keisam, Santosh; Tuikhar, Ngangyola; GAGARA, MARIAMA; FAROUGOU, SOUAÏBOU; Jeyaram, Kumaraswamy (My University, 2019)
Traditional Wagashi cheese and fermented cow milk are among the most popular dairy products appreciated by people from Benin, Niger, and the neighboring region. These products are the main source of protein in the diet of the low-income population in the region. The fermented milk is prepared by spontaneous fermentation without back-slopping. Whereas, the leaf extract of Calotropis procera is used for curdling the milk to prepare the soft Wagashi cheese. The present study aims to provide indepth analysis of yeast communities associated with these traditional milk products by high-throughput Illumina MiSeq amplicon sequencing of internal transcribed spacer (ITS) region of fungal rRNA genes. A total of 60 samples, 20 samples of fermented milk each from Benin and Niger, and 20 samples of Wagashi cheese from Benin were used for analysis. The metagenomic investigation revealed that Kluyveromyces marxianus, Saccharomyces cerevisiae, Candida parapsilosis, and Sagenomella keratitidis were the predominant yeast species present in the traditional milk products. Furthermore, we noticed a high presence of K. marxianus (61.1% relative abundance) in the Wagashi cheese and S. cerevisiae (28.4% relative abundance) in the fermented milk of Niger. The presence of potential pathogenic yeast C. parapsilosis and S. keratitidis in these African milk products calls for further investigation to assess their safety. The predominant yeast K. marxianus and S. cerevisiae, recognized with generally regarded as safe (GRAS) status, could be further selected as starter culture along with lactic acid bacteria for developing controlled fermentation processes with enhanced product quality and safety.
Keywords: Wagashi; Calotropis; MiSeq amplicon sequencing; internal transcribed spacer; Kluyveromyces; Saccharomyces; Sagenomella